ATLAS IBL: integration of new HW/SW readout features for the additional layer of Pixel Detector - Bruni, Graziano; Bruschi, M.; D'Antone, I.; Dopke, J.; Falchieri, D.; Flick, T.; Gabrielli, A.; Grosse-Knetter, J.; Joseph, J.; Krieger, N.; Kugel, Andreas; Morettini, P.; et al. (Journal of Instrumentation, 2011)
An additional inner layer for the existing ATLAS Pixel Detector, called Insertable B-Layer (IBL), is under design. The front-end electronics features a new readout ASIC, named FE-I4, which requires new off-detector electronics, currently realized with two VME-based boards: the Back Of Crate module (BOC) implements optical I/O functionality and the ReadOut Driver module (ROD) implements data processing functionality, plus a Timing Interface Module (TIM). This paper presents a proposal for the IBL readout system, mainly focusing on the ROD board.
Gesehen am 24.06.2022